Do Gender and Business Trainings Affect Business Outcomes? Experimental Evidence from Vietnam - Bulte, Erwin; Lensink, Robert; Vu, Nhung (Management Science, 2017)
We use a randomized control trial to evaluate the impact of a business training for female clients of a microfinance institution in northern Vietnam, and we consider the impact on (i) business knowledge, (ii) practices, and (ii) outcomes, as well as (iv) firm entry and exit decisions. In addition, we vary the nature of the intervention by inviting husbands to participate in the trainings for a subsample of our respondents. To gauge both short-term and medium-term effects, we combine data from two separate postintervention surveys. We find evidence of economically substantive impacts on knowledge, practices, and outcomes, and on the extensive margin (entry and exit). We also document that it takes time for the “downstream” outcomes of the trainings to materialize; although we find evidence of medium-term effects, no such evidence exists for the short term. Inviting husbands to participate in the trainings does not affect any of our knowledge or practice measures, but we document weak evidence for differential impact on (agricultural) sales and profits. Data, as supplemental material, are available at http://dx.doi.org/10.1287/mnsc.2016.2472 . This paper was accepted by Uri Gneezy, behavioral economics.